Gaming Technology in Pediatric Cerebral Palsy and Related Neuromuscular Conditions: A Scoping Review. - Stevenson, Jordan; Martin, Susanna E; English, Mahala G; Pawliuk, Colleen; Robillard, Julie M (NeuroRehabilitation, 2026)
Background: Children with cerebral palsy (CP) and related neuromuscular conditions often experience barriers to physical activity due to motor and cognitive impairments. Active video games (AVG), with or without adaptive technologies (AT), have demonstrated potential to improve outcomes in these populations. Objective: This scoping review mapped existing research on AVG and AT in pediatric CP and related neuromuscular conditions, summarizing intervention characteristics and effects on physical, cognitive, and quality of life (QoL) outcomes. Methods: The review followed PRISMA-ScR guidelines. Four databases were searched up to November 2025 (MEDLINE, Embase, Web of Science, and IEEE Xplore), supplemented by a manual citation search using Google Scholar. Eligible studies included participants under 18 years with CP and related neuromuscular conditions, reported physical, cognitive, or QoL outcomes, employed AVG, virtual/augmented reality, or gamified interventions, and were peer-reviewed and published in English. Results: A total of 192 studies were included, of which 178 examined the impact of AVG and immersive technology on physical outcomes in children with either CP (n = 173), muscular dystrophy (n = 7), or CP and a mix of related conditions (n = 12). Fewer studies included cognitive (n = 17) and QoL (n = 46) outcome measures. Findings highlighted substantial heterogeneity in study design, outcome measures, gaming devices, and AT implemented, limiting comparability and generalization. Despite this variability, AVG interventions seemed to improve patient outcomes, especially in physical function. Conclusion: We underscore the need for standardized measures to guide the development of gaming interventions that benefit patient outcomes.